Out-of-plane behavior of masonry infilled RC frames based on the experimental tests available: a systematic review - Furtado, André (2019)
The primary objective of this manuscript is to present a systematic review of experimental studies regarding infill masonry walls out-of-plane (OOP) behaviour. An extended database was built containing information from each experimental campaign and specimen tested. Parameters such as geometric dimensions, material and mechanical properties, test setups and loading protocols and test results were collected. A systematic review methodology s conducted with the aim of filter the more relevant work in this field. For the analysis of each parameter in the infill wall OOP performance, three different groups were defined: as built specimens, specimens with previous in-plane damage and retrofitted specimens. Comparisons were drawn between the specimens of each group to assess the impact of those parameters on the panel response. Empirical relationships were proposed to predict the infill panels OOP capacity according to the aspect ratio, panel slenderness, percentage of masonry units’ voids, masonry properties and previous in-plane drift. The results demonstrated that previous damage caused by in-plane tests that reached a maximum drift until 1.25% can reduce about 70% the OOP capacity of the panel, changing the failure mode of the panel that can result in fragile collapses. It was also observed that the parallel flexural strength parallel to the horizontal bed joints can increase the panel OOP maximum strength until 5 times.